2015
DOI: 10.1007/s11684-015-0412-0
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor signaling in hematopoietic homeostasis and the pathogenesis of hematologic diseases

Abstract: Toll-like receptors (TLRs), which are found in innate immune cells, are essential mediators of rapid inflammatory responses and appropriate T-cell activation in response to infection and tissue damage. Accumulating evidence suggests that TLR signaling is involved in normal hematopoiesis and specific hematologic pathologies. Particular TLRs and their downstream signaling mediators are expressed not only in terminally differentiated innate immune cells but also in early hematopoietic progenitors. Sterile activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 161 publications
(201 reference statements)
0
12
0
4
Order By: Relevance
“…The increased expression of TLRs ( Tlr1 , Tlr9 , and Tlr13 ) and TNF family members along with activated non‐canonical NF‐κB pathway suggested that inflammatory responses were also involved in the observed HSPC defects (Fig. A) . Consistent with the enhanced inflammatory response, Ly6a (Sca1), a direct target of interferon‐γ, was upregulated (Fig.…”
Section: Resultsmentioning
confidence: 81%
“…The increased expression of TLRs ( Tlr1 , Tlr9 , and Tlr13 ) and TNF family members along with activated non‐canonical NF‐κB pathway suggested that inflammatory responses were also involved in the observed HSPC defects (Fig. A) . Consistent with the enhanced inflammatory response, Ly6a (Sca1), a direct target of interferon‐γ, was upregulated (Fig.…”
Section: Resultsmentioning
confidence: 81%
“…Both TLR2 and TLR4 are expressed on the cell surface of macrophages and signal via the common adaptor protein MyD88 (11,20). IL-6 is a proinflammatory cytokine secreted by macrophages that leads to the recruitment of neutrophils to the sites of infection (18,20).…”
Section: Discussionmentioning
confidence: 99%
“…Канцерогенез в коже зависит от повышенной экспрессии TLR4 миелоидными и эпителиальными клетками, а также от наличия TLR4 эндогенного лиганда -HMGB1 (high-mobility group protein B1). Факт, что TLR4 оказывает защитную роль в невоспалительной модели канцерогенеза кожи, предполагает, что влияние TLR4 на рак кожи может зависеть от условий микроокружения опухоли [7,51]. В поджелудочной железе ингибирование TLR4 уменьшает рост опухоли, в то время как постоянное воздействие ЛПС ускоряет прогрессирование рака.…”
Section: Abstract: Innate Immunity Toll-like Receptors (Tlr) Chemokunclassified
“…Сотни SNPs (single nucleotide polymorphisms) были идентифицированы в генах TLRs, но связь с функцией не была раскрыта в подавляющем большинстве. Существует множество работ, описывающих ассоциацию полиморфных маркеров в генах TLRs и с инфекционными заболеваниями, и с образованием опухолей [7,39]. К TLR2-подсемейству относятся TLR2, TLR1 и TLR6, которые имеют высокую степень гомологии, следует отметить, что гены TLR1 и TLR6 образуют кластер с геном TLR10 в районе 4p14.…”
Section: ассоциация полиморфизмов в генах Tlrs с раз витием опухолевоunclassified